Template-based fluoropolymer ferroelectrets with multiple layers of tubular channels - Altafim, R. A. P.; Qiu, X.; Wirges, W.; Altafim, R. A. C.; Basso, H. C.; Gerhard, R.; Chinaglia, D. L. [UNESP]; Jenninger, W.; Wagner, J.; IEEE (Ieee, 2010)
Significant efforts are devoted to developing new ferroelectrets with well-controlled void distributions or uniform voids and with good long-term and thermal stability of the piezoelectricity. Here, we describe the concept, the fabrication, and the most relevant properties of fluoropolymer ferroelectret systems with three separate films of fluoroethylenepropylene (FEP), alternating with two polytetrafluoroethylene (PTFE) templates. The FEP films are selectively fused by means of a lamination process. Two practically identical PTFE templates are used, which have parallel rectangular openings (1.5x30 mm2) separated by PTFE ridges of 1.5 mm width. After removing the PTFE templates, a three-layer FEP-film sandwich with tubular channels is obtained. We demonstrate that such FEP-film systems exhibit significant and stable piezoelectricity after charging under a high DC voltage. The resulting piezoelectric effect may be further improved by carefully assembling and arranging the PTFE templates during preparation.